PENGARUH IMPULSE BUYING DAN FREKUENSI KUNJUNGAN TERHADAP NIAT PEMBELIAN PADA SITUS TOKOPEDIA DI KOTA DENPASAR - Ramadhan, Fariz; Jatra, I Made (E-Jurnal Manajemen; Vol 7 No 2 (2018)DO - 10.24843/EJMUNUD.2018.v7.i02.p08, 2018)
The rise of goods through cyberspace provides a new thing in the buying and selling industry of goods in Indonesia. Any necessities such as clothing, electronic equipment and other necessities are provided and traded online. Tokopedia includes online trading sites that can provide that. The use of advertising by the Tokopedia party in introducing the site not only raises impulse buying from consumers but also the tendency of consumers to visit the site. The purpose of this study is to explain the influence of impluse buying on buying intention and explain the influence of visit frequency to purchase intention at Tokopedia. This research has population that is user of Tokopedia site in Denpasar City. Determination of sample by purposive sampling with criterion of respondent is user of Tokopedia online website which domiciled in Denpasar City. Sample size in this study as many as 170 respondents using multiple linear regression analysis model. The results of the study indicate that impulse buying and frequency of visits have a positive effect on the Tokopedia online site. Limitations of this research are still general, so the resulting data is not specific. It is hoped that further research can be more specific. Keywords : impulse buying, visit frequency, purchase intention, online trading site.